2005
DOI: 10.1021/jf0514827
|View full text |Cite
|
Sign up to set email alerts
|

Fumonisin Production by Fusarium verticillioides Strains Isolated from Maize in Mexico and Development of a Polymerase Chain Reaction to Detect Potential Toxigenic Strains in Grains

Abstract: Fumonisins are mycotoxins produced by Fusarium verticillioides (Sacc. Nirenberg) in maize (Zea mays L.), a staple crop in Mexico. In this study, we report the isolation and identification of 67 Fusarium strains isolated from maize kernels collected in Northwest and Central Mexico. The strains were characterized regarding fumonisin B(1) production and the presence of the FUM1 gene. F. verticillioides was the predominant species isolated in both geographic regions, but the isolates from Northwest Mexico produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 37 publications
5
29
1
1
Order By: Relevance
“…All biochemicals were obtained from Sigma Chemical Co (St. Louis, MO). MY3 strain was isolated previously from maize seeds and identified as FB1-producing strain (Sánchez-Rangel et al 2005).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…All biochemicals were obtained from Sigma Chemical Co (St. Louis, MO). MY3 strain was isolated previously from maize seeds and identified as FB1-producing strain (Sánchez-Rangel et al 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Reverse transcription was performed with 1 lg of RNA using ImProm-II reverse transcriptase (Promega) and 1 lL of 500 lg/lL oligo dT (5 0 -TTTTTTTTTTTTTTTTTTTTTTTTTVN-3 0 ). Specific oligonucleotides for the amplification of FUM1 gene (accession number AF155773) were [FUM53F (5 0 -CTT GAACGCGGAGCTAGATTAT-3 0 ) and FUM53R (5 0 -AT CCGTGTATGCATATGTCGAG-3 0 )] that amplifies a 354 bp fragment (Sánchez-Rangel et al 2005) and used in this study. Tubulin gene was amplified as control using the primers 5 0 -TGCTCATTTCCAAGATCCGCG-3 0 and 5 0 -GTAGTTGAGGTCACCGTAGGAGG-3 0 that amplifies a 233 bp fragment (Hu et al 2009).…”
Section: Rna Extraction and Rt-pcr Amplificationmentioning
confidence: 99%
See 2 more Smart Citations
“…3). Sanchez-Rangel et al (2005) reported the association of FUM1 gene with fumonisin production in 54 isolates of F. verticillioides, except in seven that did not synthesize FB1 in spite of containing the gene. Another study reported that all the F. proliferatum (40.9%) isolates from asparagus contained FUM1 and FUM8 genes and also produced fumonisins ranging from 28 to 4202 lg/g in maize cultures (Wang et al 2010).…”
Section: Lc/ms Analysis For Fb1mentioning
confidence: 99%